Investigation of the effect of aging on the thermodynamic parameters and the intrinsic healing capability of graphene oxide modified asphalt binders. (10th January 2020) - Wang, Riran; Qi, Zemin; Li, Ruixia; Yue, Jinchao
Highlights: The asphalt binders were modified with GO powder and were aged in RTFOT and UV process. GO can increase the thermodynamic parameters of asphalt binders. The intrinsic healing capacity of asphalt binder was improved by GO. RTFOT aging increases SFE and promotes the intrinsic healing process, while UV aging decreases SFE and thus weaken the intrinsic healing capacity of GO modified asphalt binders. SFE values of GO modified asphalt binders are in good agreement with intrinsic healing capabilities. Abstract: Aging has a significant impact on the surface free energy (SFE) of asphalt binders and there has not been a consensus understanding of the underlying mechanism to date. Both thermodynamic properties and intrinsic healing behavior of asphalt binders are related to SFE. Graphene oxide (GO) holds the potential to improve the SFE of asphalt binders and mixtures. In this research, the effect of aging on thermodynamic parameters and intrinsic healing capability of GO modified asphalt binders was investigated. Aged asphalt binders were obtained by the rolling thin film oven test (RTFOT) and the ultraviolet (UV) aging test. The sessile drop method was adopted to measure the contact angle of probe liquids on the asphalt binders and aggregates to calculate the thermodynamic parameters based on the surface physicochemical theory. In addition, a two-piece healing (TPH) test was used to evaluate the intrinsic healing capacity of GO modified asphalt at different degrees of aging, and the initial healing rate ( R0 ) and intrinsic value at 3600 s [ Rh (3600s) ] were analyzed as measures of the overall intrinsic healing capacity. The results illustrated that SFE values of asphalt binders were increased with addition of GO. The greater the dosage of GO, the better the thermodynamic performance, and the better the intrinsic healing behavior. Both thermodynamic parameters and intrinsic healing capacity of GO modified asphalt binders increased after RTFOT aging and decreased after UV aging, and the results of R0 and Rh (3600s) demonstrated that the overall intrinsic healing capability showed the same trend as the SFE response after aging. Moreover, the development trend for initial intrinsic healing is like the development trend of SFE of asphalt binders of different types at various degrees of aging, and higher SFE can improve intrinsic healing capabilities of asphalt binders.